Information Literacy Skills in Speech- Language Pathology Students: Skill Differences Across Academic Levels. - Ratcliff, Ann; Swartz, Bradford; Ivanitskaya, Lana (Contemporary Issues in Communication Science & Disorders)
Purpose: An increasingly important aspect of university programs in communication sciences and disorders is making students aware of evidence-based practice (EBP). One of the components of EBP is information literacy, or the ability to conduct effective information searches and examine quality indicators of the information found. The information literacy skills of communication sciences and disorders students at 3 academic levels in 1 training program were measured to determine the nature and extent of any differences in the skills across academic levels. Method: The communication sciences and disorders version of the Research Readiness Self-Assessment (RRSA; Ivanitskaya, O'Boyle, & Casey, 2006) was administered to 150 students enrolled in sophomore-, senior-, and graduate-level courses in a communication sciences and disorders program. This web-based assessment measures students' skills in finding and evaluating information from a variety of sources related to speech-language pathology. The results were analyzed to determine how information literacy differed across the 3 academic levels. Results: There were significant differences among student groups in the objectively measured skills related to searching for and evaluating information. For the most part, graduate-level students demonstrated the highest skills, followed by senior- and sophomore-level students. Conclusion: Implications for communication sciences and disorders training programs are discussed, as are ways to facilitate students' information literacy skills.